2007
DOI: 10.1186/ar2144
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid peripheral blood phagocytes are primed for activation but have impaired Fc-mediated generation of reactive oxygen species

Abstract: Significant levels of circulating immune complexes (ICs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…The assessment of chemiluminescence produced by one neutrophil confirmed that neutrophils of arthritic rats responded excessively to PMA stimulation and synthesized more radicals than neutrophils of healthy controls. A similar priming of peripheral neutrophils was observed in [38][39][40] . These alterations were ascribed to the direct effect of proinflammatory cytokines on neutrophil NADPH oxidase activity, which was induced by the increased phosphorylation of p47 phox , extracellular signal-regulated kinase, and p38 mitogen-activated protein kinase [39,41] .…”
Section: Discussionsupporting
confidence: 55%
“…The assessment of chemiluminescence produced by one neutrophil confirmed that neutrophils of arthritic rats responded excessively to PMA stimulation and synthesized more radicals than neutrophils of healthy controls. A similar priming of peripheral neutrophils was observed in [38][39][40] . These alterations were ascribed to the direct effect of proinflammatory cytokines on neutrophil NADPH oxidase activity, which was induced by the increased phosphorylation of p47 phox , extracellular signal-regulated kinase, and p38 mitogen-activated protein kinase [39,41] .…”
Section: Discussionsupporting
confidence: 55%
“…However, there is a need to re-evaluate these data and to consider whether complement receptors are activated in RA neutrophils. Recent evidence suggests that neutrophils from RA patients have a functional impairment in FcRgIIa-and FcRgIIIb-mediated ROS production compared to age-and sex-matched controls (65). In this latter study, the defect in neutrophils from RA patients to produce ROS upon FcgIIa=FcgIIIb heterologous crosslinking was not a consequence of changes in FcgIIa=FcgIIIb expression, since identical levels of FcgIIa=FcgIIIb were observed in neutrophils from RA patients when compared to controls (65).…”
mentioning
confidence: 67%
“…Recent evidence suggests that neutrophils from RA patients have a functional impairment in FcRgIIa-and FcRgIIIb-mediated ROS production compared to age-and sex-matched controls (65). In this latter study, the defect in neutrophils from RA patients to produce ROS upon FcgIIa=FcgIIIb heterologous crosslinking was not a consequence of changes in FcgIIa=FcgIIIb expression, since identical levels of FcgIIa=FcgIIIb were observed in neutrophils from RA patients when compared to controls (65). Collectively these data suggest that neutrophils from RA patients may have impaired amplification of Fcg receptor function that contribute to neutrophil hyporesponsiveness and further exacerbate the susceptibility and morbidity to infection.…”
mentioning
confidence: 99%
“…These ICs were used in the assay systems as suspensions, having been gently homogenized by inversion immediately before use. It is noteworthy that an IC formed by an antibody produced in rabbits is efficient stimulus for human neutrophils activation, as reported in the literature [22,[32][33][34].…”
Section: Immune Complex (Ic)mentioning
confidence: 52%